Comparative study on the effects of Nb and V on the nucleation and growth of pearlite in high-carbon steels using in-situ method - Keduo Yu; Mingxing Zhou; Min Zhu; Houxin Wang; Zhenye Chen; Weifan Yin; Xue Su; Junyu Tian; Guang Xu (Journal of Materials Research and Technology)
The formation of pearlite in three high-carbon steels with different Nb and V additions was directly observed using a high-temperature laser scanning confocal microscope. The number densities and growth rates of pearlite nodules, and the overall pearlite transformation kinetics of pearlite were measured based on the in-situ observation results. The results show that Nb and V increase the pearlite nucleation rate due to different mechanisms. The refinement of prior austenite grain by Nb and the promotion of intragranular pearlite nucleation by V separately increase the nucleation rate. The formation of grain boundary pearlite and intragranular pearlite compete with each other in the V microalloyed steel, and the contribution of intragranular pearlite on the nucleation rate continuously increases as the transformation proceeds. In addition, the pearlite growth rate is reduced by Nb and V, resulting in the retardation of overall transformation kinetics. Moreover, the promotion of Nb on pearlite nucleation rate and its hindrance on pearlite growth and overall transformation kinetics are more pronounced than those of V.